2020
DOI: 10.1007/s40258-020-00599-0
|View full text |Cite
|
Sign up to set email alerts
|

Economic Modelling of Screen-and-Treat Strategies for Brazilian Women at Risk of Hereditary Breast and Ovarian Cancer

Abstract: Background Clinical evidence supports the use of genetic counselling and BRCA1/2 testing for women at risk for hereditary breast and ovarian cancer. Currently, screen-and-treat strategies are not reimbursed in the Brazilian Unified Healthcare System (SUS). The aim of this modelling study was to evaluate the cost effectiveness of a gene-based screen-and-treat strategy for BRCA1/2 in women with a high familial risk followed by preventive interventions compared with no screening. Methods Adopting the SUS perspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(68 citation statements)
references
References 60 publications
0
65
0
3
Order By: Relevance
“…Table 2 summarizes the application of utility for the selected studies. For all models except four [ 18 , 19 , 20 , 21 ], an adjustment for both age and target population was made. For combining data on utility, in six modeling studies the authors declared to have used the multiplicative method [ 18 , 19 , 22 , 23 , 24 , 25 ], while the remaining studies did not report the method.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 summarizes the application of utility for the selected studies. For all models except four [ 18 , 19 , 20 , 21 ], an adjustment for both age and target population was made. For combining data on utility, in six modeling studies the authors declared to have used the multiplicative method [ 18 , 19 , 22 , 23 , 24 , 25 ], while the remaining studies did not report the method.…”
Section: Resultsmentioning
confidence: 99%
“…Por esse motivo, a estimativa de custo do câncer neste estudo é considerada conservadora (SIQUEIRA et al, 2017). De acordo com o Banco Mundial, em 2010 os custos com saúde representaram 17,02% nos EUA, 10,2% na UE, 9,51% no Reino Unido, 8,27% no Brasil e 6,79% na Coreia do Sul (CORREA-GALENDI et al, 2020). A razão custo-efetividade calculada no estudo de Correa-Galendi et al (2020) chegou à conclusão de que está abaixo do limite de custo-efetividade proposto pela Organização Mundial da Saúde (OMS) recomendado para países de renda média (ou seja, 1 a 3 do PIB per capita).…”
Section: Resultados E Discussão Dos Resultadosunclassified
“…Two studies have examined the cost effectiveness of genetic testing for hereditary breast and ovarian cancer patients with SUS coverage, and propose that inclusion of this technology in this health care system is justified. In 2020, Simoes Correa-Galendi et al 169 reported that the incremental cost-effectiveness ratio for testing at-risk patients for BRCA1/2 mutations, calculated from the SUS perspective, is close to the cost-effectiveness threshold proposed by the WHO for lower middle-income countries (LMICs). Before this publication, Ramos et al 170 showed that genetic testing for BRCA1/2 in high-risk patients with SUS coverage was cost effective when genetic testing was expanded and prophylactic measures were adopted for family members (cascade testing).…”
Section: Tp53 In Southern and Southeastern Brazilmentioning
confidence: 92%